Getting a Good Press - Pierce, Peter (LiNQ (Literature in North Queensland), 2016)
Peter Pierce reviews; The Writer’s Press 1948—1998, Edited by Craig Munro, University of Queensland Press, 329pp. 29.95 ISBN 0 7022 3005 7.